INDO PENTA KILL’S AND ITS BUCIN PHENOMENON EFFECT TOWARDS THEIR MEMBERS - I Gusti Ngurah Octova Seventilofa (Sekolah Tinggi Pariwisata Mataram, 2021)
This study aims to explain the old phenomenon that has recently re-emerged and become viral among adolescents called bucin or 'slaves of love'. This research is the implementation of qualitative research. Data collection uses direct interview and observation techniques in a Whatsapp group chat. The sample is the members of the Indo Penta Kill Gamer Community. The total sample of this study amounted to 12 people where the sample was determined or selected using the simple random sampling technique. The result of this research is that the bucin phenomenon arises because of the urge to want to be loved, to love, and to find the identity from the players or members of the Indo Penta Kill community. The bucin phenomenon affects several aspects of the personal life of the perpetrator, for example, daily habits and time management